2011
DOI: 10.1016/j.econedurev.2010.06.015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol use on academic achievement in high school

Abstract: This paper examines the effects of alcohol use on high school students’ quality of learning. We estimate fixed-effects models using data from the National Longitudinal Study of Adolescent Health. Our primary measure of academic achievement is the student’s GPA abstracted from official school transcripts. We find that increases in alcohol consumption result in small yet statistically significant reductions in GPA for male students and in statistically non-significant changes for females. For females, however, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
92
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 41 publications
9
92
1
5
Order By: Relevance
“…For instance Ding et al (2009), García-Gómez et al (2013), Fletcher (2014), Sabia (2007), Balsa et al (2011) and Pieterse (Forthcoming) identify a negative relationship between poor general health, health shocks, ADHD, body weight, alcohol usage and maltreatment respectively on the one hand and academic performance on the other hand. In addition, Bharadwaj et al (2013) reveal a positive relationship between early health interventions and academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…For instance Ding et al (2009), García-Gómez et al (2013), Fletcher (2014), Sabia (2007), Balsa et al (2011) and Pieterse (Forthcoming) identify a negative relationship between poor general health, health shocks, ADHD, body weight, alcohol usage and maltreatment respectively on the one hand and academic performance on the other hand. In addition, Bharadwaj et al (2013) reveal a positive relationship between early health interventions and academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Others have found early alcohol use is weakly associated with lower school grades (Crosnoe et al, 2012)and future educational achievement (Latvala et al, 2014), particularly for males (Balsa et al, 2011).…”
mentioning
confidence: 99%
“…The study further found that there was also a significant relationship between academic achievement and anti-social behaviour of female secondary Biology students. Balsa et al (2011)estimated fixed-effects models using data from the National Longitudinal Study of Adolescent Health and found that increases in alcohol consumption result in small yet statistically significant reductions in GPA for male students and in statistically non-significant changes for females. For females, however, higher levels of drinking result in self-reported academic difficulty.…”
Section: Discussion Of Findingsmentioning
confidence: 99%